Enhancing institutional research capacity in the midst of a pandemic: A system approach. Issue 187 (1st November 2021) - Atchison, Eric S.
Abstract: This article outlines the impacts of COVID‐19 on higher education and provides a contextual assessment of how higher education systems can provide support to institutions and stakeholders through a formulated planning process which helps identify, plan, and achieve strategic goals in response to fluctuating priorities.